Literary cubism in the scientific discourse of the 20th – 21st centuries - Ivanova, Natallia S. (Journal of the Belarusian State University. Philology, 2024)
The article clarifies the concept of literary cubism as an avant-garde movement that took shape in French poetry and spread in the literature of different countries. The aesthetic and poetic principles characteristic of cubism are highlighted, confirming the intermedial connections between literature and painting of that time. Particular attention is paid to the creative mutual influence of poets and artists of the avant-garde era. The interpretation of literary cubism in the modern scientific paradigm is revealed, as well as the reception of this concept in literary schools of different countries, which allows us to justify its use in the framework of the study of the creative heritage of French avant-garde poets (G. Apollinaire, B. Cendrars, P. Reverdy, etc.). Theoretical and practical significance of the study lies in a holistic consideration of the concept of literary cubism, which denotes an important phenomenon in world art of the first half of the 20th century.
Keywords: avant-garde; intermediality; cubist poetry; literary cubism; simultaneity; modern literary criticism